2020
DOI: 10.1186/s13024-020-00383-7
|View full text |Cite|
|
Sign up to set email alerts
|

Divergence, Convergence, and Therapeutic Implications: A Cell Biology Perspective of C9ORF72-ALS/FTD

Abstract: Ever since a GGGGCC hexanucleotide repeat expansion mutation in C9ORF72 was identified as the most common cause of familial amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), three competing but nonexclusive hypotheses to explain how this mutation causes diseases have been proposed and are still under debate. Recent studies in the field have tried to understand how the repeat expansion disrupts cellular physiology, which has suggested interesting convergence of these hypotheses on downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 146 publications
1
13
0
Order By: Relevance
“…Herein, we found that RAB39B deficiency resulted in elevated LC3B-II levels by impairing autophagic flux at basal level; and this is consistent with the elevated PI3K-AKT-mTOR signaling upon loss of Rab39b since this mTOR signaling inhibits autophagy (Dibble and Cantley, 2015). Coincidently, the C9ORF72/WDR41/SMCR8/ATG101 complex acts as a GDP/GTP exchange factor for RAB39B and deficiency in components of this complex can also alter autophagy, implying that such alterations may be mediated by RAB39B (Sellier et al, 2016;Yang et al, 2016;Corbier and Sellier, 2017;Tang et al, 2020). Moreover, we found that treatment with the mTOR inhibitor rapamycin comparably stimulated autophagy in both control and RAB39B-deficient cells, suggesting that RAB39B deficiency impairs basal autophagic flux but fails to affect cellular response to autophagy simulation.…”
Section: Discussionsupporting
confidence: 75%
“…Herein, we found that RAB39B deficiency resulted in elevated LC3B-II levels by impairing autophagic flux at basal level; and this is consistent with the elevated PI3K-AKT-mTOR signaling upon loss of Rab39b since this mTOR signaling inhibits autophagy (Dibble and Cantley, 2015). Coincidently, the C9ORF72/WDR41/SMCR8/ATG101 complex acts as a GDP/GTP exchange factor for RAB39B and deficiency in components of this complex can also alter autophagy, implying that such alterations may be mediated by RAB39B (Sellier et al, 2016;Yang et al, 2016;Corbier and Sellier, 2017;Tang et al, 2020). Moreover, we found that treatment with the mTOR inhibitor rapamycin comparably stimulated autophagy in both control and RAB39B-deficient cells, suggesting that RAB39B deficiency impairs basal autophagic flux but fails to affect cellular response to autophagy simulation.…”
Section: Discussionsupporting
confidence: 75%
“…This suggests the merit of ASO targeting STMN2 cryptic splicing for clinical application. TDP-43 also acts as a main repressor of the inclusion of UNC13A cryptic exons, which is a genetic risk factor for ALS and frontotemporal dementia (FTD) (Brown et al, 2022;Koike et al, 2023;Ma et al, 2022;Mehta et al, 2023). How the inclusion of UNC13A cryptic exons is involved in the pathogenesis of these ALS/FTD remains to be elucidated.…”
Section: Cryptic Rna Splicings Of the Targets Of Tdp-43mentioning
confidence: 99%
“…Two C9orf72 HRE-mediated toxic gain of function mechanisms have been proposed and reviewed: namely RNA toxicity mediated by intranuclear RNA foci and dipeptide repeat protein (DPR) inclusions from uncanonically translated HRE transcripts [ 10 ]. In addition, loss of function of the C9orf72 protein has been proposed as a pathogenic mechanism, however, whilst reduced C9orf72 function has been shown to exacerbate gain of toxicity mechanisms [ 221 ], loss of the protein is insufficient to recapitulate a disease phenotype in mammals [ 191 ]. With respect to hnRNPs, the loss of function of the C9orf72 protein has thus far not been linked to a dysregulation of hnRNP biology.…”
Section: Hnrnps and Ftld/als Pathologiesmentioning
confidence: 99%